IMPLICATIONS OF HUMAN-WILDLIFE CONFLICT ON LOCAL LIVELIHOOD: CASE STUDY, KIMBI-FUNGOM NATIONAL PARK CAMEROON - ANGWAFO, TSI Evaristus; BENAZIA, NKENGAFAC Michael; CHUO, MVO Denis (International Journal of Research -GRANTHAALAYAH, 2020)
This study entitled “implications of human-wildlife conflict on local livelihood in the Kimbi-Fungom National Park” was undertaken to assess impacts of Human-Wildlife Conflict (HWC) in the Park so as to provide basis to design a sustainable wildlife conservation roadmap. Data collection was done using questionnaires, semi structured interviews and direct observations. Collected data were treated using excel and statistical package for social sciences (SPSS version 14). Findings revealed that, 98% of the population experience human-wildlife conflicts that negatively impacted local livelihood, with cumulative average financial losses amounting to 1, 97,890 FCFA/year/acre (0.40ha) for the six common staple food crops, and an average cumulative surface area damage of 4.75 acres/year (0.19ha). It was revealed that great proximity to the Park edge bear the highest cost of the conflict. Though losses varied with different crop and distance from the Park, this was attributed to population pressure that intensifies farming activities along the Park edge that greatly threatened the sustainable management of wildlife in the study area. It is against this background that an Integrated Conservation Development Project is proposed for a sustainable wildlife management roadmap that would have to confront the drivers of conflict by working hand-in-hand with all stakeholders concerned towards a win-win outcome.